2018
DOI: 10.1016/j.jtho.2018.01.019
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Systemic Therapy in the Management of Stage I Large Cell Neuroendocrine Carcinoma of the Lung

Abstract: In this largest-reported retrospective study of patients with resected stage I LCNEC, survival was improved in patients who received chemotherapy in both stage IA and stage IB LCNEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 35 publications
(46 reference statements)
5
55
1
1
Order By: Relevance
“…Similar results were obtained by other authors, such that 3-and 5-year recurrence-free survival was reported in 45% and 38-39.3% of patients, respectively [3,30,34]. Many recurrent tumors as distant metastases were observed in LCNEC patients with complete resection [20,21,37]. Therefore, surgery alone could be insufficient to treat patients with LCNEC and adjuvant therapy may be necessary [36,38].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar results were obtained by other authors, such that 3-and 5-year recurrence-free survival was reported in 45% and 38-39.3% of patients, respectively [3,30,34]. Many recurrent tumors as distant metastases were observed in LCNEC patients with complete resection [20,21,37]. Therefore, surgery alone could be insufficient to treat patients with LCNEC and adjuvant therapy may be necessary [36,38].…”
Section: Discussionsupporting
confidence: 85%
“…Most data are based on retrospective analysis. Kujtan L et al [21] conducted a retrospective evaluation of LCNEC patients with surgically resected stage I of the disease and found that improved survival was achieved by chemotherapy in both stage IA and IB patients.…”
Section: Introductionmentioning
confidence: 99%
“…There are limited studies assessing how age impacts prognosis due to the low incidence of pulmonary LCNEC. Kujtan and colleagues reported that patients over 70 had worse survival outcomes (Kujtan et al 2018). Additionally, Wu et al confirmed that age was a prognostic factor for pulmonary neuroendocrine tumors, which, however, only included 23 patients (5.7%) with pulmonary LCNEC (Wu et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…L-LCNEC patients treated by surgery alone were rarely cured even in the early stage [26], which urges more scholars to consider chemotherapy or radiotherapy [6,18,27,28]. Two retrospective analysis showed that compared with the patients with surgery alone, platinum-based neoadjuvant chemotherapy or postoperative adjuvant chemotherapy could prolong the recurrence time of tumor and significantly benefit the longterm survival for the patients with early stage [29,30]. Chemotherapy regimens for small cell lung cancer/non-small cell lung cancer were used in L-LCNEC treatment, but most of the data were came from single center, small sample or retrospective studies, and the results were controversial [7,31,32].…”
Section: Discussionmentioning
confidence: 99%